PRICING METHODS IN SPORTS - Petković, Branko; Životić, Dragan; Mitić, Milovan (Scientific Journal Management in Sports, 2015)
The subject of this paper is to present the most important methods when it comes to pricing. Price is the main element of a marketing strategy because it is the only one that generates revenue, unlike other marketing mix instruments that generate costs. No matter how good sports products and services are, how creative the promotion is and how efficient the distribution is, a sports organization will incur losses if the price does not cover the costs. Therefore, it is important that marketing managers in sports understand the methods and the complexity of decisions in pricing because in this way they will decisively influence the position of the sports organization in the market, its competitiveness and profitability. The aim of this paper is to describe pricing methods as key processes affecting the profitability of a sports organization. On the other hand, a sports organization ‘s policy on pricing is based on the goals and methods of pricing, which should strategically influence the extent of the impact on the sports market by providing a recognizable image of the organization and its products/services to the sports consumers. In the paper, the methods of analysis and synthesis were used, and so were deductive and inductive methods.